Faktor-faktor yang mempengaruhi niat beli dengan perceived quality sebagai variabel moderasi menggunakan pendekatan planned behavior theory - Riza, Riza Ihsani; Rofiuddin, Mohammad (Nur Science Institute, 2024)
The purpose of this study was to determine the effect of lifestyle, attitude, and religiosity on purchase intention with perceived quality as a moderating variable. This type of research is a quantitative study with a population of consumers of Rocket Chicken products spread throughout the city of Salatiga. The sampling technique in this study used purposive sampling totaling 100 respondents. The analytical technique used is Moderated Regression Analysis (MRA). The statistical test results show that attitude and religiosity have a positive effect on purchase intention, Meanwhile, lifestyle hurts purchase intention. Perceived quality can moderate the influence of lifestyle, attitude, and religiosity on purchase intention.